Radial Interaction for Corrosion Defects in Offshore Pipeline - Mohamad Arba’i, Nurul Afiqah (IRC, 2016)
Carbon steel pipeline had been trusted as the most reliable and safest way to transmit the fluid from the sources to the consumers. Like any other structural behaviour, this carbon steel tends to fails and require further maintenance after certain period of time. One of the major threats that cause this problem is corrosion activity that acted on the both sides of pipeline wall, internal and external. This affects the pipeline integrity and strength due to the reduction of the wall thickness that caused by metal deterioration. Throughout this project, the study will be more focused into the defects interaction between external and internal sides of pipeline wall in order to know the defects interaction behaviour radially. Numerical method which is finite element analysis is used as a medium to approach this problem. The research and analysis will be conducted using ANSYS to see the pipeline impact in terms of structure deformation, equivalent elastic strength, equivalent stress and strain energy and etc. From the finite element modelling generated, the load limit of the pipe is determined based on the maximum von Mises distribution graph plotted. Through comparing predicted failure pressure using proposed solution as well as experimental results in previous literature study, the accuracy of proposed solution is demonstrated consequently.